Remote managers are having trust issues - Parker, Sharon; Knight, Caroline; Keller, Anita (Harvard Business School Publishing, 2020)
Covid-19 has thrust many leaders into remote management which requires a different skill set than face-to-face management. They have been forced to make this transition quickly, and for the most part, without training. While some jobs have proven adaptable, many sectors are not well-suited for the remote environment and many workers have home lives that present overwhelming challenges. As a result, some managers may be finding their roles more difficult than before — and making their subordinates’ lives more stressful as they struggle to adapt. Even prior to the pandemic, managing teleworkers presented unique obstacles. Research shows that managers who cannot “see” their direct reports sometimes struggle to trust that their employees are indeed working. When such doubts creep in, managers can start to develop an unreasonable expectation that those team members be available at all times, ultimately disrupting their workhome balance and causing more job stress.